2021
DOI: 10.3390/nursrep11020038
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing the Nursing Profession in Saudi Arabia: An Integrative Review

Abstract: There is a paucity of recent literature identifying the issues facing the nursing profession in Saudi Arabia. The aim of this integrative review is to highlight the ongoing challenges facing the nursing profession in Saudi Arabia despite attempts to make a difference and suggests recommendations for the future. Literature published from 2000 to 2020, inclusive, relevant for nursing challenges in Saudi Arabia was accessed and reviewed from multiple sources. In Saudi Arabia, inadequate numbers of Saudi nurses ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 31 publications
(114 reference statements)
2
46
0
Order By: Relevance
“…Furthermore, work and living conditions for expatriate nurses in Saudi Arabia are considered to be poor, adding to that religious and cultural differences, and language barriers create complex working environment and social living conditions for them. 13 Therefore, many expatriate nurses initially come to Saudi Arabia to gain work experience, and they tend to move to developed countries in the west and Europe after acquiring enough skills and expertise. 14 Therefore, not only the barriers to the expatriates but also the job dissatisfaction and turnover are few other issues affecting the nursing sector in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, work and living conditions for expatriate nurses in Saudi Arabia are considered to be poor, adding to that religious and cultural differences, and language barriers create complex working environment and social living conditions for them. 13 Therefore, many expatriate nurses initially come to Saudi Arabia to gain work experience, and they tend to move to developed countries in the west and Europe after acquiring enough skills and expertise. 14 Therefore, not only the barriers to the expatriates but also the job dissatisfaction and turnover are few other issues affecting the nursing sector in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction, autonomy of work, and resource adequacy reflected more strong correlations with task, contextual, and adaptive performance; and all types of commitment. As identified in the previous studies (12,14,15,26,38), job satisfaction, one of the important 'quality of work-life' subscale was identified to be significantly influencing job performance and organization loyalty. Thus, it can be analyzed and concluded that quality of work-life can moderately influence the organization loyalty and job performance of the nurses in Saudi Arabia, based on the hypothesis analysis.…”
Section: Discussionmentioning
confidence: 61%
“…Focusing on the expatriate nurses, several issues such as poor living and working conditions, cultural differences, communication problems, complex social living conditions are affecting their work-life in the country ( 12 ), as a result of which their satisfaction levels and loyalty are decreasing. For instance, it was identified that many expatriate nurses initially come to Saudi Arabia even though the working and living conditions are poor, only to gain enough work experience, so that they can later move to the developed countries such as the US and the UK, where they can experience better work-life conditions ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…during their mid-careers [29], hence, restarting their counting for years of service. Finally, under profile variable, our results suggest that having an administrative role predicted lower anxiety among female nursing faculty.…”
Section: Recommendationsmentioning
confidence: 99%